2005
DOI: 10.1128/jcm.43.4.1963-1967.2005
|View full text |Cite
|
Sign up to set email alerts
|

Identity and Prevalence of Multilocus Sequence Typing-Defined Clones of Group A Streptococci within a Hospital Setting

Abstract: , 121 clinical isolates of group A streptococci (GAS) were collected from a London hospital and characterized by multilocus sequence typing (MLST) to determine the identity and prevalence of clones circulating within this setting. A total of 39 sequence types (ST), of which 20 were represented by a single isolate, were identified. The eight most prevalent clones among the 121 GAS were ST117/emm81 (16%), ST39/emm4 (9%), ST62/emm87 (7%), ST28/emm1 (6%), ST36/emm12 (6%), ST46/emm22 (5%), ST334/emm82 (5%), and ST1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
19
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 41 publications
(29 reference statements)
6
19
0
Order By: Relevance
“…Three of the CCs displayed the erm(TR)-encoded MLS B phenotype and were coresistant to tetracycline. ST46 in CC1 has been associated with erm(B), mef(A/E), or macrolide susceptibility in other countries (20,28,36), whereas ST63 in CC2 contained erm(TR) in Poland and Germany in accordance with our findings (28,36). The remaining six strains in CC2 belonged to ST369, which is a single locus variant (SLV) of ST63 not previously registered in the MLST database.…”
Section: Erm(b) and Mef(o) Were Exclusively Associated With Tet(m) Wsupporting
confidence: 71%
See 2 more Smart Citations
“…Three of the CCs displayed the erm(TR)-encoded MLS B phenotype and were coresistant to tetracycline. ST46 in CC1 has been associated with erm(B), mef(A/E), or macrolide susceptibility in other countries (20,28,36), whereas ST63 in CC2 contained erm(TR) in Poland and Germany in accordance with our findings (28,36). The remaining six strains in CC2 belonged to ST369, which is a single locus variant (SLV) of ST63 not previously registered in the MLST database.…”
Section: Erm(b) and Mef(o) Were Exclusively Associated With Tet(m) Wsupporting
confidence: 71%
“…CC4 was monoresistant to macrolides due to mef(A). This clone has previously been observed in Finland, Germany, Spain, and England (14,20,26,28).…”
Section: Erm(b) and Mef(o) Were Exclusively Associated With Tet(m) Wmentioning
confidence: 98%
See 1 more Smart Citation
“…M-protein gene (emm) typing has been useful as a simple genetic tool for identifying and resolving Streptococcus pyogenes strains for epidemiologic studies (18,27,29,35). This is consistent with the observation that within given regions, group A streptococcal (GAS) emm types are often restricted to only one or two defined clonal complexes, and often, these common clones are predominant in diverse locations (15) (available at www.mlst.net).…”
supporting
confidence: 49%
“…GAS epidemiological investigations have benefited from MLST data; Sakota et al (2006) observed that genetic diversity amongst superficial GAS strains from Nepal was remarkably higher than that of strains from the USA, aiding the delineation of GAS clones and elucidating their distribution in different parts of the globe. In hospital settings it can add valuable information to determine the distribution of clones and any possible change in prevalent types, which might signify the appearance of more virulent and successful clones (McGregor & Spratt, 2005). Strain characterization by MLST is sometimes combined with PFGE.…”
Section: Discussionmentioning
confidence: 99%